Postglacial range expansion shaped the spatial genetic structure in a marine habitat‐forming species: Implications for conservation plans in the Eastern Adriatic Sea. (29th October 2018) - Ledoux, Jean‐Baptiste; Frleta‐Valić, Maša; Kipson, Silvija; Antunes, Agostinho; Cebrian, Emma; Linares, Cristina; Sánchez, Pablo; Leblois, Raphael; Garrabou, Joaquim
Abstract: Aim: Understanding how historical and contemporary processes shaped and maintain spatial patterns of genetic diversity is a major goal for conservation biologists. Here, we characterized the pattern of neutral genetic diversity and we inferred underlying processes in the habitat‐forming octocoral Paramuricea clavata in the Adriatic Sea, a peculiar phylogeographic region of the Mediterranean Sea. Location: Eastern coast of the Adriatic Sea. Methods: We genotyped seven microsatellites in 454 individuals of P. clavata from 13 populations recolonized after the Last Glacial Maximum (LGM). We estimated the levels of contemporary connectivity and genetic drift and we reconstructed the demographic history of these populations. Results: The pattern of spatial genetic structure resulted from the combination of hierarchical genetic clusters and isolation by distance (IBD). A significant decrease in genetic diversity and an increase of the frequencies of individual alleles likely due to allele surfing from the south to the north of the area were observed as expected after a postglacial sequential recolonization. Based on maximum likelihood analyses, the foundation of these populations was not linked to dramatic change in population size. Main conclusion: Oceanographic barriers to gene flow combined to the restricted dispersal of P. clavata likely maintain the hierarchical structure and the IBD pattern. We suggest that the latitudinal genetic gradient results from a northward "serial founder events" recolonization. By integrating patterns and processes, we bridge the gap between the evolutionary and the conservation biology of P. clavata, providing management guidelines, which will benefit the associated coralligenous biodiversity.